Localization of 99mTc-GRP Analogs in GRPR-Expressing Tumors: Effects of Peptide Length and Neprilysin Inhibition on Biological Responses - Aikaterini Kaloudi; Emmanouil Lymperis; Panagiotis Kanellopoulos; Beatrice Waser; Marion de Jong; Eric P. Krenning; Jean Claude Reubi; Berthold A. Nock; Theodosia Maina (MDPI AG, 2019)
The overexpression of gastrin-releasing peptide receptors (GRPRs) in frequently occurring human tumors has provided the opportunity to use bombesin (BBN) analogs as radionuclide carriers to cancer sites for diagnostic and therapeutic purposes. We have been alternatively exploring human GRP motifs of higher GRPR selectivity compared to frog BBN sequences aiming to improve pharmacokinetic profiles. In the present study, we compared two differently truncated human endogenous GRP motifs: GRP(14–27) and GRP(18–27). An acyclic tetraamine was coupled at the N-terminus to allow for stable binding of the SPECT radionuclide 99mTc. Their biological profiles were compared in PC-3 cells and in mice without or with coinjection of phosphoramidon (PA) to induce transient neprilysin (NEP) inhibition in vivo. The two 99mTc-N4-GRP(14/18–27) radioligands displayed similar biological behavior in mice. Coinjection of PA exerted a profound effect on in vivo stability and translated into notably improved radiolabel localization in PC-3 experimental tumors. Hence, this study has shown that promising 99mTc-radiotracers for SPECT imaging may indeed derive from human GRP sequences. Radiotracer bioavailability was found to be of major significance. It could be improved during in situ NEP inhibition resulting in drastically enhanced uptake in GRPR-expressing lesions.